Proceso operativo del camal municipal y sus efectos en la calidad ambiental de la ciudad de Vinces. Año 2014. Plan de reingeniería - León Aguirre, José Francisco (2015)
The research was aimed to evaluate the operational process of the slaughterhouse and its impact with the impact that the environment which it was found that this process prejudice the abiotic components cause, directly affecting people who live around them and indirectly to the population in general. It has used scientific research methods to obtain information, mainly inductive - deductive method in order to analyze the problem situation to obtain possible solutions that contribute to environmental improvement of the municipal slaughterhouse to perform processes whose main priority care and use of environmentally friendly techniques. The study was conducted through visits to the slaughterhouse, to verify the process of slaughtering of cattle. The administrator (a) interviews were conducted to obtain information specific stages of slaughter processes, surveys of people living around the slaughterhouse, matrices conformities are also used for compliance with environmental health laws and finally taking samples of liquid discharges to be analyzed. In these analyzes it was found to exceed the permissible effluent discharge limits freshwater stipulated in the text Secondary Environmental Legislation in the parameters BOD5, COD and suspended solids, as these liquid discharges receive no treatment. Reengineering Plan is presented in order to prevent, control and / or mitigate negative impacts of the processes and that result in a benefit of a better quality product for consumers